THEORETICAL AND LEGAL MODEL OF CRIMINALIZATION OF SOCIALLY DANGEROUS ACTS RELATED TO THE CONDUCT OF ECONOMIC OR OTHER ACTIVITIES IN TERRITORIES THAT ARE ASSIGNED TO THE CATEGORY OF DANGEROUS OR POTENTIALLY DANGEROUS (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to the analysis of the legal regulation of mine action in Ukraine and the search for ways to improve the efficiency of mine action and protect citizens from the dangerous effects of the consequences of war by means of criminal legislation of Ukraine. Based on the results of the systemic legal analysis of the legal regulation of mine action in Ukraine, the author proposes to introduce criminal liability for conducting economic or other activities in the territories classified as dangerous or potentially dangerous. The author also emphasises the expediency of providing at the legislative level for the possibility of a subsidiary criminal law response to the involvement of legal entities as economic and other entities in violations of the requirements of legislation related to the conduct of economic or other activities in the territories classified as dangerous or potentially dangerous, the essence of which would be to apply to the involved legal entities the criminal law measures provided for in Section XIV-I of the General Part of the Criminal Code of Ukraine.
Keywords: criminalization; introduction of criminal liability; economic activity; mine action; demining; non-compliance; improper compliance; criminal liability; punishment; criminal law measures; legal entity; fine; confiscation of legal entity property; liquidation of a legal entity; additional (non-financial) criminal law measures